REE Anomalies Changes in Bottom Sediments Applied in the Western Equatorial Atlantic Since the Last Interglacial - Sousa, Thiago A.; Venancio, Igor Martins; Marques, Eduardo Duarte; Figueiredo, Thiago S.; Nascimento, Rodrigo Azevedo; Smoak, Joseph M.; Albuquerque, Ana Luiza S.; Valeriano, Claudio Morisson; Silva-Filho, Emmanoel Vieira (Frontiers in Marine Science, 2022)
We reconstruct paleoredox conditions in the Western Equatorial Atlantic (WEA) over the glacial-interglacial cycle ( 130 ka) by using new high-resolution REEs data and their anomalies from a marine sediment core (GL-1248) collected from the equatorial margin off the continental shelf of NE Brazil. This approach aims to improve the understanding of the dynamics of paleoclimatic and sedimentary inputs on the coast of northeastern Brazil. Marine sediments were analyzed via Mass Spectrometry (ICP-MS) after total digestion with HF/HNO3. REEs proxies are a useful tool in understanding the transport and origin of sediments due to their physicochemical properties. Our data showed the Parnaíba River was the main source of REEs content in the western South Atlantic. Fe minerals (Fe-oxyhydroxides) produced via weathering of continental and tropical soils were the principal REE-carrier phase during transportation and ultimate deposition at core site GL-1248. Several regional climatic factors mainly rainfall changes contributed significantly to continental-REEs erosion of sedimentary layers of the Parnaíba Basin, and transport and deposition of the mobilized REEs from the continent to the study site. Furthermore, changes in the negative Ce-anomaly showed low variation along the core indicating a reduction in deep ocean oxygenation during the interglacial relative to the last glacial period. That variation, probably, was associated with glacial-interglacial variations in sea level with the exposure of the continental shelf. The origin of positive Eu anomalies in siliciclastic sediment, also observed in the core, was explained by preferential retention by feldspars such as plagioclases and potassium feldspars mostly from the assimilation of felspar during fractionation crystallization of felsic magma in the Parnaíba basin since the Last Interglacial.